On the bacteriostatic activity of hyaluronic acid composite films. (15th May 2021) - Zamboni, Fernanda; Okoroafor, Chinonso; Ryan, Michael P.; Pembroke, J. Tony; Strozyk, Michal; Culebras, Mario; Collins, Maurice N.
Highlights: Heterogenous crosslinking reaction of HA and HA-CNF films using di-isocyanate. Bacteriostatic properties of HA depend on molecular weight. In vitro antimicrobial activity of high molecular weight HA. Abstract: Biofilm-related infections and contamination of biomaterials are major problems in the clinic. These contaminations are frequently caused by Staphylococcus aureus and are a pressing issue for implantable devices, catheters, contact lenses, prostheses, and wound dressings. Strategies to decrease contamination and biofilm related infections are vital for the success of implantable biomaterials. In this context, hyaluronic acid (HA), a naturally derived carbohydrate polymer, known to be biocompatible, degradable, and immunomodulatory, has shown some antimicrobial activity effects. Due to its poor structural stability, crosslinking strategies, and the incorporation of reinforcing fibres in HA gels is required to produce tailored gels for varying applications. Whilst carbon-based reinforcing materials, such as carbon nanofibers (CNF), present some intrinsic antimicrobial activity related to their high surface area, herein, a crosslinking strategy to enhance the mechanical properties and regulate the rate of degradation of HA is presented. We utilise bis-(β-isocyanatoethyl) disulphide (BIED) as the crosslinker with the gel reinforced using 0.25 wt% CNF. The effects of CNF and BIED on the structural, mechanical, thermal, and swelling behaviour are examined. These new HA derivatives exhibit excellent mechanical properties and are capable of withstanding physiological stresses in vivo . Antimicrobial activity of the HA derivatives were tested against Staphylococcus aureus and the results reveal antibacterial effect. These carbohydrate based materials have potential application on surfaces within clinical settings where staphylococcal contamination is currently an issue.